Impact of non-steroidal anti-inflammatory drugs on cardiovascular risk: Is it the same in osteoarthritis and rheumatoid arthritis?. Issue 4 (4th July 2017) - Bournia, Vasiliki-Kalliopi; Kitas, George; Protogerou, Athanasios D.; Sfikakis, Petros P.
Abstract: Although large-scale population studies have shown that non-steroidal anti-inflammatory drugs (NSAIDs) increase the risk of myocardial infarction, this is not confirmed in patients with rheumatoid arthritis (RA). Herein, we review the litterature on the differential effects of NSAIDs on cardiovascular risk in osteoarthritis (OA) versus RA and discuss possible explanations for this discrepancy. To assess a potential additive effect of age in non-RA populations, we compared weighted mean age between RA patients and unselected NSAID users included in cohort and case–control studies that estimate the cardiovascular risk of NSAIDs, assuming that the main indication for NSAID usage in elderly populations is OA. Our hypothesis that advanced age in osteoarthtitis compared to RA patients confounds the effect of NSAIDs on cardiovasular risk was not confirmed. Several other hypotheses that can be proposed to explain this counterintuitive effect of NSAIDs on the cardiovascular risk of RA patients are discussed. We conclude that patients with RA have a lower cardiovascular disease risk associated with the use of NSAIDs, probably due to the nature of their disease per se, until further research indicates differently.